To Pray According to the Example of Christ - Mari Jože Osredkar (Edinost in Dialog)
This paper presents three modes of Christian prayer, each grounded in different forms of belief and biblical figures. Adam believed he did not need God and that he could achieve salvation on his own. He trusted in himself and in the power of his own decisions and actions. His prayer is characterized as magic. Christians at this stage of belief are convinced that mere words and actions can fulfil their desires. Cain offered his produce to God, believing in God's responsiveness to his wishes. When he was not heard, he became angry. Similarly, Christians at this second stage of belief try to persuade God to fulfil their desires, threatening to abandon Him if He does not comply, just as Cain abandoned God. Abraham is the initiator of »faith in faith«, which allows him to unconditionally accept God's will. He believed in God's faith, meaning that God knew Abraham would adhere to His commandments. The Gospels also present Jesus' prayer as a request for »Thy will be done, Father!«. This represents the most perfect form and ideal of Christian prayer.